[P138] The dosimetric impact of breast tissue expander with metallic ports in helical tomotherapy: A rando-phantom study. (August 2018) - Lee, Hsing-Yi; Tu, Pei-Chih; Lin, Chia-Hong; Lui, Louis Tak; Shaw, Suzun; Wu, Ching-Jung; Nien, Hsin-Hua
Abstract : Purpose: Increasing number of breast cancer women receiving post-mastectomy radiation therapy (PMRT) had immediate two-stage tissue expander (TE)/implant for breast reconstruction. TEs with metallic port become popular due to convenient saline injection. Previous studies showed 10–30% actual dose reduction under tangential beam arrangement caused by high Z material. This study was conducted to quantify the dosimetric effects in the region of the metallic ports using helical tomotherapy. Methods: Bolus with 0.5 cm thickness was placed on the surface of rando-phantom simulating post mastectomy pectoralis major and skin beyond as layer M. TE with different capacities (100 cc, 150 cc, 200 cc, 250 cc, and 300 cc) was placed under layer M simulating treatment condition. 1 cm bolus was placed on layer M for routine PMRT technique. Artifact removement and heterogeneity correction of simulation image were performed via tomotherapy planning system. Two tomotherapy plans were generated for each capacity of TE: Plan A) artifact removed; Plan B) artifact removed plus CT electron density 1 was assigned to the metallic port region. Radiochromic films were used for absolute dose measurement at three locations: 1) surface of layer M; interface between 2) TE and layer M 3) bottom of TE. Film QA was utilized for dose analysis. Results: The distance between TE top and metallic port is range from 0.7 for small capacity to 1.0 cm for large capacity. The distance between metallic port and TE bottom is range from 0 to 1.4 cm along with increasing capacity. The measured dose at layer M surface was range from −0.53% to −8.9% and −0.39% to −8.29% for plan A and B. The measured dose at interface between TE and layer M was range from 1.09% to −6.01% and 1.92% to −6.09% for plan A and B. The measured dose at bottom of TE was range from −0.14% to −7.57% and 1.08% to −5.37% for plan A and B. Conclusions: The actual dose under helical tomotherapy for patient with metallic port breast tissue expander is acceptable comparing to tangential technique. TEs with 100 cc and 150 cc have higher metallic port position reproducibility. Helical tomotherapy is a suitable treatment technique for patient with breast tissue expander with metallic port.